As perspectivas do banimento do amianto para a economia do Estado de Goiás e para o município de Minaçu - Silva, Cristina Socorro da (2002)
This study aims to analyze the importance of the asbestos substance to regional and state level and the economic impacts that occurred after the closing of the international market for its commercialization, emphasizing the trade balance, tax collection, labor market, income of the municipality of Minaçu and the State of Goiás from the production of ore and commercialization of the product. For greater understanding of the reader, studies and diagnoses raised about the real aggression are addressed ore and its derivatives to human health and the environment, in addition to measures national and international environmental protection measures taken, and products substitutes with alternative. The methodology adopted in the execution of the work was bibliographical selection and analysis in books, magazines, periodicals and specialized websites, field research and interviews conducted in the city of Minaçu: at the company SAMA S.A., in the city hall and agenfa; in addition to research in state and federal agencies, linked to the mineral sector such as: AGIM - GO, DNPM - 6th DS / GO, DNPM - Headquarters, ETERNIT S.A, MIC - SECEX, MME and, the economy of the State of Goiás as: finance departments, farm, planning and budget. The statistical data were collected using as basis of publications: Brazilian Mineral Yearbook (AMB), Brazilian Mineral Summary (SMB), Brazilian Mineral Balance (BMB), Social Balance of the company SAMA S.A. in addition the Lavra Annual Report, Brazilian Institute of Geography and Statistics (IBGE). For analysis of the effects of ore and product on the environment and human health, the data were acquired through contacts in national bodies linked to the problem of such as: ABICRISO, ABIFIBRO, ABRA, AEREA, CEA, CNI, CNTI, CONAMA, EPM, GIS, INCOR, INSER, IPT, UNICAMP and USP, in magazines specialized companies such as FORBES, and international bodies such as: EPA, NCR, WHO. AND after the development of the study, we concluded that the economy of the municipality of Minaçu will be seriously compromised if the ore is banned, impacting the economic growth of the municipality, considering that its main activity economy and tax collection in the 1990s was the mining industry chrysotile asbestos ore and export of its fibers, inducing multiplier effects and stimulating the formation of non-basic activities, generating demand for goods and services. However, there will be no significant impact on the regional economy of State of Goiás, considering the small participation of the mineral sector as a source generating income and employment in relation to other sectors such as agriculture and livestock. It was observed throughout the research that synthetic fibers have not yet been developed with viable physical and economic characteristics to national and international mainly for the civil construction sector in the popular housing sector.